1992
DOI: 10.1159/000187069
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement in Leptospirosis: A Pathophysiologic Study

Abstract: The kidney involvement in leptospirosis appears to be a special form of acute renal failure due to a higher frequency of polyuric forms and the presence of hypokalemia with an elevated urinary fractional excretion of potassium. Using a clearance technique, we detected higher fractional urinary potassium excretion in leptospirotic guinea pigs (26.5 ± 4.7%) than in normal animals (14.1 ± 2,8%, p < 0.05). After blocking distal NaCl reabsorption with furosemide, it was observed that in leptospirotic animals both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 15 publications
1
41
1
7
Order By: Relevance
“…That GLP inhibits Na,K-ATPase-mediated transport in rat thick ascending limb cells may appear at variance with the report of Magaldi et al (31) who showed that MTAL from normal and leptospirotic guinea pigs display similar transport capacity when microperfused in vitro. In fact, two explanations may account for this apparent discrepancy.…”
Section: Discussioncontrasting
confidence: 66%
“…That GLP inhibits Na,K-ATPase-mediated transport in rat thick ascending limb cells may appear at variance with the report of Magaldi et al (31) who showed that MTAL from normal and leptospirotic guinea pigs display similar transport capacity when microperfused in vitro. In fact, two explanations may account for this apparent discrepancy.…”
Section: Discussioncontrasting
confidence: 66%
“…In rabbit renal tubule epithelial cells, GLP inhibits sodium-potassium ATPase (Na,K-ATPase) pump activity in a dose-dependent manner (47). This may explain some electrolytic alterations observed in leptospirosis patients with acute renal failure (1,26,36). In experimental models with guinea pigs injected with pathogenic L. interrogans, GLP can be detected in the damaged tissues adhering to endothelial cells and to epithelial membranes, accompanying other antigen deposits resulting from bacterial destruction by the immune system (3,25).…”
mentioning
confidence: 99%
“…The collecting tubules of those animals proved to be resistant to vasopressin action. 39 Recently, a clinical study with 20 patients infected with leptospirosis has shown the presence of proteinuria in all cases, hypermagnesuria in 75%, reduced tubular reabsorption in 50%, and reduced phosphate reabsorption in 45% of the patients. 43 …”
Section: Prerenal Aki and Hemodynamic Alterationsmentioning
confidence: 99%
“…36,37,38 Experimental and clinical studies have shown that those findings result from injury to the proximal tubule and resistance of the medullary collecting tubule to vasopressin. 14,30,39 The injury of the proximal tubule leads to a reduction in the proximal reabsorption of sodium. The resistance of the medullary collecting tubule to vasopressin leads to a defect in the urinary concentration, causing polyuria.…”
Section: Prerenal Aki and Hemodynamic Alterationsmentioning
confidence: 99%